HMGB1-Mediated Early Loss of Transplanted Islets Is Prevented by Anti–IL-6R Antibody in Mice. Issue 1 (January 2015) - Itoh, Takeshi; Nitta, Tomoyuki; Nishinakamura, Hitomi; Kojima, Daibo; Mera, Toshiyuki; Ono, Junko; Kodama, Shohta; Yasunami, Yohichi
<x xml:space="preserve">Abstract</x> Objectives The limited success in achieving insulin independence of patients with type 1 diabetes mellitus after islet transplantation from a single donor, mainly due to early loss of transplanted islets, hampers clinical application of islet transplantation. Previously, we have shown in mice that the early loss of transplanted islets in the liver, the site of islet transplantation, is caused by innate immune rejection triggered by high-mobility group box 1 (HMGB1) protein released from transplanted islets. We herein determined whether the HMGB1-mediated early loss of transplanted mouse islets is prevented by anti–interleukin-6 receptor (IL-6R) antibody. Methods The effect of anti–IL-6R antibody on amelioration of hyperglycemia in streptozocin-induced diabetic mice receiving 200 islets into the liver from a single donor was evaluated in association with HMGB1-stimulated interferon-γ production of hepatic mononuclear cells. Results Hyperglycemia of diabetic mice receiving 200 syngeneic islets was ameliorated with down-regulation of interferon-γ production of hepatic natural killer T cells and neutrophils when anti–IL-6R was administered at the time of transplantation. This beneficial effect was also seen in allografts when alloimmune rejection was prevented by anti-CD4 antibody. Conclusions These findings demonstrate that anti–IL-6R antibody prevented the early loss of intrahepatic islet grafts with inhibiting HMGB1-induced immune activation after islet transplantation.